Triple layered core–shell ZVI@carbon@polyaniline composite enhanced electron utilization in Cr(vi) reduction. Issue 24 (5th June 2018) - Gong, Kedong; Hu, Qian; Xiao, Yangyi; Cheng, Xiang; Liu, Hu; Wang, Ning; Qiu, Bin; Guo, Zhanhu
Abstract : PANI and carbon layers in the ZVI@C@PANI enhanced H + capture and electron utilization in the Cr(vi ) reduction for an enhanced Cr(vi ) removal performance. Abstract : A triple layered core–shell structured zero valence iron@carbon@polyaniline (ZVI@C@PANI) nanocomposite was synthesized and was used to reduce the Cr(vi ) in wastewater. The synthesized ZVI@C@PANI was demonstrated to have a great Cr(vi ) removal performance with a fast rate and high capacity. ZVI@C@PANI can reduce almost all the hexavalent chromium (Cr(vi )) (1.0 mg L −1 ) Cr(vi ) in 5 min, and has a maximum capacity of 508 mg g −1 . A maximum Cr(vi ) removal capacity of 508 mg g −1 was achieved. The shell layers of C@PANI were demonstrated to be important to improve the electron utilization of the inner ZVI. The PANI shell captured and stored the H + from the solution, providing an acidic condition on its surface. The carbon layer can adjust the H + and H2 transfer in the ZVI@C@PANI. These were disclosed as the mechanisms for the improved electron utilization by this core–shell structured ZVI@C@PANI.